Estrategias metacognitivas para mejorar la comprensión lectora de los estudiantes del sexto grado de la Unidad Educativa Dr. Manuel Cabrera Lozano, período 2023-2024 - Jaramillo Granda, Luz María (2024)
The general objective of the research entitled Metacognitive strategies to improve reading comprehension was to determine the contribution of metacognitive strategies to improve the reading comprehension of sixth grade students of the Unidad Educativa Dr. Manuel Cabrera Lozano; in order to meet the objective, three specific objectives were set: to determine the contribution of metacognitive strategies to improve reading comprehension of sixth grade students of the Unidad Educativa Dr. Manuel Cabrera Lozano. Manuel Cabrera Lozano Educational Unit; in order to fulfill the objective, three specific objectives were proposed: to identify the metacognitive strategies applied in the reading comprehension process by the teacher; to determine the students' reading comprehension level; and to design alternative guidelines on metacognitive strategies; To make this research effective, the mixed approach was used with a descriptive type of research and non-experimental design, during the process the scientific, inductive, deductive, analytical, synthetic and statistical methods were applied, the techniques used were the observation sheet, survey and interview, as instruments direct observation guide, open questions guide and structured questionnaire, which contributed significantly to data collection, the research population was in the sixth grade; through a non-probabilistic sampling, 29 students and a teacher were selected. The results obtained from the research indicate that metacognitive strategies contribute significantly to improve reading comprehension in students, so the teacher must be in constant preparation in these strategies, which will allow her to impart her knowledge in a creative and innovative way. Thus, it is concluded that metacognitive strategies are of great importance to improve reading comprehension in students, thus developing their reading skills and abilities, with this, students will have the ability to understand the reading and give their own criteria about it, as well as to make their learning meaningful and lasting.